(untitled) (Research, Society and Development, 2022)
The use of barbed wire fences is a very common practice in several regions of the world, for the delimitation of lands and other environments. However, for some time now, some discussions have already been addressed about the danger that these fences cause to fauna, in groups of small to large animals, winged or terrestrial, among them bats. Thus, the present study aims to describe a record of a bat found dead entangled in a barbed wire fence. This incident occurred in a rural area of the municipality of Chã Grande (8° 13’ 57’’S, 35° 27’ 43’’W) in the interior of the state of Pernambuco, Northeastern Brazil. The record refers to an adult male of Carollia perspicillata, which was trapped by the endopatagium. This was the first record of this incident type for the species in Brazil. Although the control of natural traps is not within our reach, it is our duty to seek alternatives that minimize this problem associated with human traps such as fences and wires. For this, there should initially be awareness of not using barbed wire fences, as well as becoming aware of other precautions that can be taken in cases where the use is already made, in order to minimize the impacts on wildlife. Even if some strategies are not totally efficient, many of them reduce the impacts on the fauna, protecting the species and ensuring their perpetuation.